DINAMIKA KARYA TAFSIR AL-QUR’AN PESANTREN JAWA - Baidowi, Ahmad; Ma’rufah, Yuni (STAI AL-ANWAR SARANG, 2022)
Examining Indonesian Qur'anic interpretation works cannot exclude the study of Interpretation books written by Islamic scholars, clerics, and intellectuals from the pesantren community. This paper proves that the interpretation works from Islamic boarding schools continue to develop dynamically in various aspects, whether the format, the script and language used, the method of interpretation, and the interpretation. This fact confirms that the writings of the interpretation by some writers from Pesantren are based on the needs of the community, its audience, and readers. Furthermore, the interpretation works from Pesantren show that Pesantren has very positive responses to various changes and concerns to the intellectualism movement with its uniqueness and characteristics.